Popis kosca Crex crex v Jovsih - Ferlan, Tea (Acrocephalus, 1998)
In 1998, the pupils of the Kapele Primary School, the members of the Youth Section of the Kapele Tourist Association and their mentors carried out a survey of the Corn Crake at Jovsi Nature Monument with its predominating inundated meadows of fescue and wild oat Molinio-Arrhenatheretea and high sedge Magnocaricion. During the breeding period (from May 20th to July 1st), six night surveys were carried out. The greatest number of calling Corn Crakes (19) was registredon May 30th. In the area covering some 460 ha there ...
Keywords: ornitologija; ptice; bird